Ediarum. A toolbox for editors and developers - Mertgens, Andreas (Enthalten in:RIDE;Köln : Institut für Dokumentologie und Editorik, [2014]-;11 (01.2020);Online-Ressource)
Abstract: ediarum.DB, ediarum.BASE.edit and ediarum.REGISTER.edit are the three currently released modules of the ediarum editing environment developed by the TELOTA initiative at the BBAW in Berlin. The set of two frameworks for the Oxygen XML Editor and one exist-db application aims to support digital scholarly editors in generating and annotating TEI-XML Data. The frameworks offer a graphical interface within Oxygen XML Editor to add mark-up and metadata for a subset of TEI elements without the need of manually editing XML files. The modules are open-source and intended to be used as a starting point or toolbox for other developers to create project-specific customized frameworks. Despite some parts of the modules only being available in German as of this moment, and some need for improved documentation, the ediarum modules already offer a flexible and open way for researchers to edit their TEI data and a resource for other developers to build upon in their projects
10.18716/ride.a.11.4
Keywords: digital edition; environment; eXist-db; markup; open-source; Oxygen XML Editor; plugin; toolbox; transcription